The Art of Distances : Ethical Thinking in Twentieth-Century Literature - Stan, Corina (Book collections on Project MUSE., 2018)
In The Art of Distances, Corina Stan identifies an insistent preoccupation with interpersonal distance in a strand of twentieth-century European and Anglophone literature that includes the work of George Orwell, Paul Morand, Elias Canetti, Iris Murdoch, Walter Benjamin, Annie Ernaux, Günter Grass, and Damon Galgut. Specifically, Stan shows that these authors all engage in philosophical meditations, in the realm of literary writing, on the ethical question of how to live with others and how to find an ideal interpersonal distance at historical moments when there are no obviously agreed-upon social norms for ethical behavior.Bringing these authors into dialogue with philosophers such as Michel de Montaigne, Ralph Waldo Emerson, Friedrich Nietzsche, Sigmund Freud, Helmuth Plessner, Martin Heidegger, Jean-Luc Nancy, Emmanuel Levinas, Peter Sloterdijk, Guillaume le Blanc, and Pierre Zaoui, Stan shows how the question of the right interpersonal distance became a fundamental one for the literary authors under consideration and explores what forms and genres they proposed in order to convey the complexity of this question.Stan demonstrates that these emblematically twentieth-century authors reimagined how people can live together and provided alternatives to established ways of thinking about community. In this way, she suggests, these literary authors are engaged, albeit unknowingly, in fleshing out what Roland Barthes called "a science, or perhaps an art, of distances."